(untitled) (International Journal of Engineering and Computer Science, 2019)
Digital watermarking has become a promising research area to face the challenges created by the rapid growth in distribution of digital content over the internet. To prevent misuse of this data, digital watermarking techniques are very useful. Here, a new algorithm that can be used for copyright protection is introduced for the embedding and detection of a watermark in the domain of discrete wavelet transform (DWT). The elements of the logo watermark are embedded directly to the one-level DWT decomposed sub-bands. The experimental tests and results of this scheme have shown that the scheme has the desired properties such as invisibility and robustness